Relationship between the duration of smoking and blood pressure in Han and ethnic minority populations: a cross-sectional study in China - Yuelun Zhang; Yunying Feng; Shi Chen; Siyu Liang; Shirui Wang; Ke Xu; Dongping Ning; Xianxian Yuan; Huijuan Zhu; Hui Pan; Guangliang Shan (BMC, 2021)
Abstract Background Evidence for correlation between the cigarette use and blood pressure change remains ambiguous. This study modelled relationship between the duration of smoking and systolic blood pressure in a large national multi-ethnic cross-sectional survey in China. Methods Participants were selected through a multi-stage probability sampling procedure from 2012 to 2017. Former or current smokers were included in this study, whose smoking behaviour, blood pressure, and other demographic information were collected and measured through a face-to-face interview. Linear and non-linear relationships between the duration of smoking and systolic blood pressure were analysed and differences of the association between Han and minority populations were specially checked. Results A total of 8801 participants were enrolled in this study. Prevalence of hypertension was 41.3 and 77.8% were current smokers. For every additional year of smoking duration, systolic blood pressure raised by 0.325 mmHg (95% CI 0.296 to 0.354 mmHg, P <  0.001). The Chinese minority populations may suffer more from the elevated blood pressure in long-term smoking than Han populations (0.283 mmHg (95% CI 0.252 to 0.314 mmHg, P <  0.001) versus 0.450 mmHg (95% CI 0.380 to 0.520 mmHg, P <  0.001) raise in systolic blood pressure with each additional year of smoking in minority and Han populations). Conclusions Smoking is associated with raised systolic blood pressure in Chinese population. This association is notedly stronger in Chinese minority populations.